ASSERTIVENESS AND SUBSTANCE USE IN ADOLESCENCE: RESULTS FROM A CROSS-SECTIONAL STUDY - Suelves, Josep M.; Sánchez-Turet, Miquel (Anales de Psicología / Annals of Psychology, 2001)
Adolescent substance abuse prevention programmes often include assertiveness training as a component. This cross-sections study analyzed the relationship between scores on the Children’s Assertive Behavior Scale (Michelson y Wood, 1980) and self-reported use of tobacco, alcohol, cannabis derivatives and synthetic drugs in a sample of 294 adolescents (mean age=13,06 years, range 11-14). Respectively, 51,4% and 41,6% of subjects reported no previous use of tobacco or alcohol, but a 4,8% of daily smokers. Only a few subjects reported previous use of the remaining substances (7,1% had ever used cannabis, and 1,4% had ever used synthetic drugs). No statistically significant correlation was found between global CABS scores and substance use, but scores on the aggressivity subscale were significantly correlated with reported use of tobacco, alcohol, and cannabis derivatives.The lack of enough evidence on the relationship betweenassertiveness and substance use highlights the relevanceof carefully monitoring the outcomes of adolescent substance abuse prevention programmes.